Revenge Porn and Mental Health: A Qualitative Analysis of the Mental Health Effects of Revenge Porn on Female Survivors. (January 2017) - Bates, Samantha
This study examines the emotional and mental health effects revenge porn has on female survivors. To date, no other academic studies have exclusively focused on mental health effects in revenge porn cases. In-depth qualitative interviews were conducted between February 2014 and January 2015 with 18 female revenge porn survivors, and inductive analysis revealed participants' experiences of trust issues, posttraumatic stress disorder (PTSD), anxiety, depression, suicidal thoughts, and several other mental health effects. These findings reveal the seriousness of revenge porn, the devastating impacts it has on survivors' mental health, and similarities between revenge porn and sexual assault.